Contested landscapes of belonging at the Turkish-Syrian border :|the (re)making of Antakya and Defne - Medeiros Coelho, José Rafael. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2021., 2021)
Based on the new metropolitan municipality system (Law No. 6360) Hatay, a multicultural province located at the Turkish-Syrian border, has undergone major cartographic changes. During this process, Defne has been crafted out of Antakya city as an ethnically and religiously segregated district. In this ethnographic study, I analyze the sociopolitical implications of this process. I examine how and why the Alawite and Christian Arab communities that identify themselves as indigenous peoples of Antakya have found themselves in the newly mapped Defne. I demonstrate how and through what spatial and identity practices these indigenous communities and key political stakeholders compete over the cultural heritage of Hatay and Antakya. Doing so, I aim to reveal the power relations behind the new cartography for Hatay while witnessing and documenting Antakya's (re)make and Defne's metamorphosis into the built and imaginary landscapes of the nation at the Turkish-Syrian border. My research has shown that Defne, now with its non-Sunni population, stands as a sign of difference and segregation in Hatay’s new ethno sectarian landscape, in contrast to Antakya, which has been Sunnified due to recent official districting practices. Nonetheless, the very same place (Defne) has proven to be a new public sphere for Hatay’s Arab Alawites to negotiate their local identity by appropriating its space for political and communal engagements.
Keywords: Municipality of Metropolitan Hatay.; Multiculturalism -- Hatay -- Defne.; Social life -- Hatay -- Defne.